Scientific American Supplement, vol. xxxi, No. 804 May 30, 1891 (United States; Munn & Co.; New York, NY, 2022)
Two page from an issue of the Scientific American with cover illustration of an engraving based on Mahler portrait of Beethoven and brief description on p. 12840.